Temsirolimus in therapy of renal cell cancer - Nurzyński, Paweł; Żołnierek, Jakub; Oborska, Sylwia; Waśko-Grabowska, Anna; Rzepecki, Piotr (Contemporary Oncology/Współczesna Onkologia, 2007)
Tyrosine kinase inhibitors play the leading role in progress in therapy of renal cell cancer. The value of sunitinib and sorafenib was very well documented in many clinical trials. mTOR kinase inhibitors (CCI-779, RAD001, AP23576) are being studied and have a big chance to be approved for cancer therapy. Rapamycin, also named sirolimus, is a natural antibiotic produced by S. hygroscopicus. Initially an immunosuppressive drug, recently many clinical trials with rapamaycin derivatives are provided in different tumours. Temsirolimus (CCI-779) is a derivative of rapamycin more soluble in water. It has been studied in phase II and III trials in renal cell cancer. Phase II trial proved a clinical benefit for 51% of patients with median time to tumour progression 5.8 months and median survival 15.0 months. In the phase III trial temsirolimus gave 3.6 months (49%) improvement in median OS and 1.8 months (95%) improvement in median PFS compared with interferon (IFN). The combination of temsirolimus and interferon did not significantly improve overall survival as compared with IFN. CCI-779 was better tolerated that IFN. We think that this is a good time for combination of different drugs such as: monoclonal antibodies, kinase inhibitors, cytokines. These “cocktails” give a big chance for a patient with metastatic renal cell cancer that kidney cancer will be a chronic disease.